Tinjauan Literatur : Pengaruh Kepercayaan dan Kepuasan Pelanggan terhadap Proses Bisnis E-commerce - Kusnadi, Kusnadi; Jeni Susyanti (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2024)
The purpose of this study is to understand the role of customer trust and satisfaction in the context of e-commerce business and to explore how these two factors influence customer loyalty and online purchase decisions. The benefit of the results of this study for companies is that they can improve their marketing strategies and e-commerce services to strengthen customer trust and satisfaction. The research method used is a qualitative approach using literature studies to gain a deeper understanding of the factors that influence the variables under study. The results show that both satisfaction and trust have a significant impact in the context of e-commerce business.